Pemertahanan Bahasa Jawa di Tengah Masyarakat Multilingual Kecamatan Cot Girek - Andica Irawan; Juni Ahyar; Masithah Mahsa (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
This study aims to describe the forms of Javanese language maintenance in the multilingual community of Cot Girek District. This research is qualitative descriptive in nature. The methods used are observation and interviews. The data for this study come from the attitudes of Javanese speakers that influence Javanese language maintenance. The findings of this research indicate that Javanese speakers should use Javanese among fellow Javanese, at home, and when playing with friends, read books about the Javanese language, learn new Javanese vocabulary, frequently use it in family conversations, participate in Javanese language contests or competitions, strengthen Javanese language teaching in schools, attend Javanese language training or courses, teach Javanese to children, use social media or technology to teach Javanese, use social media accounts and follow accounts that use Javanese, raise awareness and maintenance of the Javanese language by listening to and watching Javanese songs and dramas, communicate with native Javanese speakers, engage in cultural events and traditional performances, collaborate with Javanese culture enthusiasts, develop literature, and promote legal protection for the Javanese language as an important cultural asset.